If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 2 + 6x + 7 = 52 Reorder the terms: 2 + 7 + 9x + 6x = 52 Combine like terms: 2 + 7 = 9 9 + 9x + 6x = 52 Combine like terms: 9x + 6x = 15x 9 + 15x = 52 Solving 9 + 15x = 52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 15x = 52 + -9 Combine like terms: 9 + -9 = 0 0 + 15x = 52 + -9 15x = 52 + -9 Combine like terms: 52 + -9 = 43 15x = 43 Divide each side by '15'. x = 2.866666667 Simplifying x = 2.866666667
| 3(n+5)6=3n+4 | | x+5forx=18 | | 5(8+m)+2(7+7m)=0 | | 2x+9forx=2 | | 4/5n=1 | | 6x+5x+8+3=38 | | x*.05=40 | | H/8-14=24 | | 40x^2+26x-30=0 | | -8=-2y+18 | | 3x18x5.5/y];y=0.3 | | 2m+7=6m-1 | | 4n=9m-8 | | 11x-18+40=180 | | 4x+=x+13 | | 80+x=135 | | 2(3n-5)+3n=2-n | | (7+3i)(3-7i)= | | 11x-18+40= | | -5+7t=43-y | | 10x-2x=-7 | | 11x-18+40=11x-18 | | (0.6)c-9c+6=(1.8)c+6-3 | | 40-.05=x | | 4(x-19)=12(x+1) | | 12.8/4 | | 5=3-6X-10 | | 3(2x-7)+4x=7(x+2) | | 9(8n+2)=-8(6n-8) | | 85*24m=685 | | -19+11z=-9z+20z-19 | | 7p+-4p-6=2p+8 |